177k views
4 votes
Evaluate the function found in the previous step at x=-2

Evaluate the function found in the previous step at x=-2-example-1
User Jankapunkt
by
4.5k points

1 Answer

2 votes

Given:


5x^2+2y=-3x-2y

To evaluate the function at x=-2, we simplify the given relation first:


\begin{gathered} 5x^2+2y=-3x-2y \\ \text{Simplify and rearrange} \\ 2y+2y=-3x-5x^2 \\ 4y=-3x^{}-5x^2 \\ y=\frac{-3x^{}-5x^2}{4} \end{gathered}

We let y=f(x):


f(x)=\frac{-3x^{}-5x^2}{4}

Next, we plug in x=-2 into the function:


\begin{gathered} f(x)=\frac{-3x^{}-5x^2}{4} \\ f(-2)=(-3(-2)-5(-2)^2)/(4) \\ \text{Simplify} \\ f(-2)=(-14)/(4) \\ f(-2)=-(7)/(2) \end{gathered}

Therefore,


f(-2)=-(7)/(2)

User Horace Heaven
by
4.9k points